Robotic assessment modules for upper limb stroke assessment: Preliminary study - Abdul, R. H. (American Scientific Publishers, 2016)
Conventional assessment scales are widely used to quantify motor performance in stroke survivors. Although they are widely used, there are several limitations with these assessment scales such as lack of repeatability, subjective, time-consuming and it depends on the ability of the trained physiotherapist. In contrast, robot-based assessments are highly repeatable, objective, and could potentially reduce assessment time. However, robotbased assessments are not as well established as conventional assessment scale and the correlation to conventional assessment scale is unclear. This study was to determine if there are any similarities in the movements between the proposed robotic assessment modules namely as Draw Square, Draw Diamond and Draw Circle and between the sequences, clockwise and counter clockwise on 10 male healthy subjects. Result shows that there are no similarities between each robotic assessment modules and between the sequences. All kinematic variables extracted from each robotic assessment modules can be used as benchmark for assessment purpose in stroke patient.